Alice in Wonderland [videorecording (DVD)] - Burton, Tim, 1958-; Wasikowska, Mia, 1989-; Hathaway, Anne, 1982-; Bonham Carter, Helena, 1966-; Depp, Johnny; Glover, Crispin; Rickman, Alan; Fry, Stephen, 1957-; Sheen, Michael; Spall, Timothy, 1957-; Carroll, Lewis, 1832-1898; Carroll, Lewis, 1832-1898 (Walt Disney Studios Home Entertainment : Distributed by Buena Vista Home Entertainment, 2010)
Alice, now 19 years old, returns to the whimsical world she first entered as a child and embarks on a journey to discover her true destiny.